Equine disease surveillance. (20th September 2014) - Slater, Josh
Abstract : The National Equine Health Survey (NEHS) was introduced in 2010 by the Blue Cross and British Equine Veterinary Association in response to a perceived need for some form of syndromic endemic disease surveillance in horses in the UK. Data are now collected on an annual 'snapshot' basis directly from horse owners. Here, Josh Slater discusses some of the findings from the survey carried out in 2013